2020
DOI: 10.21203/rs.2.21662/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Health Research Capacities in Palestine: High-quality and Proper Knowledge Transfer and Translation for Sound Decision-making

Abstract: Background: Over the last two decades, the World Health Organization (WHO) has proposed a global strategy and initiatives to build robust capacity for a Health Research System (HRS) focusing on Health Research Quality and Standardization (HRQS), Health Research Knowledge Transfer and Dissemination (HRKTD), and Health Research Translation and Utilization into Health Care Decisions and Policies (HRTUDP). Despite the expansion of health research productivity for several decades, HRS Capacity (HRSC) in Palestine a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 22 publications
(33 reference statements)
1
1
0
Order By: Relevance
“…However as these levels are strongly interconnected, any strength or weakness in one of these levels will directly impact the other two levels [9]. Most of the findings are consistent with the international literature on research capacity strengthening in Low and Middle Income Countries (LMICs) including those affected by armed conflict and political unrest [40,41]. The key themes emerging from this work are categorized below as strengths and challenges of health research which would support the design of impactful research capacity strengthening interventions.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…However as these levels are strongly interconnected, any strength or weakness in one of these levels will directly impact the other two levels [9]. Most of the findings are consistent with the international literature on research capacity strengthening in Low and Middle Income Countries (LMICs) including those affected by armed conflict and political unrest [40,41]. The key themes emerging from this work are categorized below as strengths and challenges of health research which would support the design of impactful research capacity strengthening interventions.…”
Section: Discussionsupporting
confidence: 75%
“…The recent work of AlKhaldi et al that focuses on research capacity strengthening in Palestine, also revealed that health research capacities in the country are relatively weak despite the recent increase in health research production. Guidelines for Health Research Quality and Standardization are not adhered to due to a lack of policies and resources, and Health Research Knowledge Transfer is a major challenge that requires contextualization and adequate implementation [41]. Regarding research skills, a needs assessment focusing on the West Bank, Palestine, published by R4HC-MENA colleagues, found that most of the respondents considered that they have a significant gap in their abilities and understanding of coding and analysis of qualitative data, and planning and designing research [86].…”
Section: Key Challengesmentioning
confidence: 99%